RESPON MASYARAKAT TERHADAP PENGOBATAN MENGGUNAKAN ARUS LISTRIK DI DESA SIDO MUKTI KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN - Maemunah, Sari; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research on treatment using electric current has the purpose of knowing the reasons why people choose this treatment and to find out how the public response to treatment uses electric current. The location of this study is located in Sido Mukti Village, Pangkalan Kuras District, Pelalawan Regency. This study uses quantitative methods with descriptive analysis, data collection techniques in this study are random sampling or taken randomly and data collection obtained based on reality in the field through questionnaires, interviews, and documentation. The research respondents consisted of 78 people. The theoretical framework used is response theory according to Soemanto. From the results of the study the majority of respondents agreed with the treatment of this electric current, this was demonstrated by the enthusiasm of the community towards some of the analysis that the author did, by looking at the economic situation which was divided into three groups in the form of low, middle and upper economic groups, based on the treatment experience of the community, especially Sido Mukti village who went to medical treatment, experienced several complaints such as getting bored medical treatment, cost factors, and efforts to get the cure forbthe disease. Besides seeing the mechanisms, procedures, and benefits, the treatment using electricity can be used as an alternative treatment especially for the people of Sido Mukti Village, Pangkalan Kuras District, Pelalawan Regency. Keywords: Response, Treatment, Electric Current